The impact of e-commerce on improving the financial performance of organisations: Amazon as a case study - Zina, Abbad (The International tax journal, 2026)
This article aims to examine the impact of e-commerce on improving the Financial performance of organisations. We have adopted a descriptive-analytical approach, beginning with an exploration of the concept of e-commerce before moving on to the financial performance of organisations, before moving on to the practical aspect, for which we have taken Amazon as a case study due to the company’s clear dominance of e-commerce. The study ultimately concluded that e-commerce has a significant impact on improving Amazon’s financial performance, given the company’s ability to sell to and deal with numerous customers from around the world without geographical restrictions and by reducing the costs associated with traditional shops, which has greatly helped it to increase its sales and, consequently, its financial revenue.